Effect of atorvastatin on oxidative stress and inflammation markers in myxomatous mitral valve disease in dogs: A comparison of subclinical and clinical stages - Patchaya Thassakorn (2019)
© 2019 John Wiley & Sons Ltd Myxomatous mitral valve disease (MMVD) is the most common acquired cardiac disorder found in dogs. The disease process can lead to heart failure (HF) and has been found to be associated with oxidative stress and inflammation. Statins exert antioxidant and anti-inflammatory effects in human HF patients. However, the beneficial effects of statins in MMVD dogs are still unclear. Thirty MMVD dogs were enrolled in the study and were divided into two groups: MMVD without HF dogs (n = 15) and MMVD with HF dogs (n = 15). Atorvastatin (8 mg kg−1 day−1) was administered orally to all dogs for 4 weeks. All dogs underwent physical examination and cardiac examination at the beginning and end of the experiment, including baseline values for hematology, blood chemistry profile, lipid profile, N-terminal pro B-type natriuretic peptide, oxidative stress marker (8-isoprostane), and inflammatory marker (tumor necrosis factor alpha). The results showed that atorvastatin reduced plasma cholesterol levels in both groups. In addition, plasma concentrations of 8-isoprostane, tumor necrosis factor alpha, and N-terminal pro B-type natriuretic peptide were significantly lower after atorvastatin administration, but only in MMVD dogs in the HF group. Atorvastatin found to be associated with possible antioxidant and inflammatory effects in dogs with HF secondary to MMVD. The potential benefits of statins in dogs with HF merits further investigation in larger, placebo-controlled studies.